GROUNDWATER FLOW MODELING FOR MANAGEMENT AND DEVELOPMENT SYSTEMS IN THE URBAN AREA OF MAJENE DISTRICT, WEST SULAWESI PROVINCE - Marwadi, Aji (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 25, No. 1, Januari 2021DO - 10.24843/JITS.2021.v25.i01.p03, 2021)
The computer-depicted groundwater model is a representation of the actual situation that represents it in the field, so that it can function as a monitoring and forecasting of a future groundwater flow system. The purpose of this study is to model groundwater flow that can represent the actual conditions that occur in the urban area of ??Majene Regency. The modeling is done numerically using Visual Modflow. The input data required are: logbor / geoelectric data correlation, the boundary of the research location to be modeled, namely the river boundary, measurement and observation of river conditions as a river boundary, groundwater recharge data (infiltration) is obtained using groundwater balance from processed data rainfall and air temperature, measurement of groundwater level as a means of determining model validation to approach real conditions in the field. The results of this study are in the form of a groundwater flow model that can be used for groundwater management systems as a decision-making tool for project planners and government agencies in predicting changes in groundwater flow systems, determining the location of development and monitoring sea water intrusion in the future. cities located on the beach.